A new exercise test for the assessment of heart failure: use of a self powered treadmill. Issue 5 (May 1989) - Parameshwar, J; Dambrink, J H; Sparrow, J; Wright, C; Park, A; Tweed, J; Poole-Wilson, P A
Abstract : Time limited exercise on a self powered treadmill was evaluated as a method of assessing functional capacity in patients with mild heart failure. The characteristics of the treadmill were established by exercising 11 controls at three speeds and two inclinations and comparing oxygen consumption with that on a motorised treadmill under the same conditions. Oxygen consumption on the self powered treadmill at an equivalent speed and inclination was significantly higher because of the work needed to overcome the friction of the belt. Unlike a conventional treadmill, increasing the gradient on the self powered treadmill did not increase oxygen consumption. The distance walked in 12 minutes on the self powered treadmill was measured in eight patients with mild heart failure and ten controls. Maximal oxygen consumption was measured in the same group on a conventional treadmill by a mass spectrometer. There was a significant correlation between the distance walked and maximum oxygen consumption. In patients with mild heart failure the distance travelled in 12 minutes on a self powered treadmill provides a practical, inexpensive, and sensitive method of assessing functional capacity.